Asymptotic homogenization modeling of smart composite generally orthotropic grid-reinforced shells: part i - theory - Challagulla, Krishna S.; Kalamkarov, Alexander L.; Georgiades, Tasos (My University, 2010)
We develop in this paper a comprehensive micromechanical model for the analysis of thin smart composite grid-reinforced shells with an embedded periodic grid of generally orthotropic cylindrical reinforcements that may also exhibit piezoelectric properties. The original boundary value problem which characterizes the thermopiezoelastic behavior of the smart shell is decoupled via the asymptotic homogenization technique into three simpler problems the solution of which permits the determination of the effective elastic, piezoelectric and thermal expansion coefficients. The general orthotropy of the constituent materials is very important from the practical viewpoint and it renders the resulting analysis a lot more complicated. In Part II of this work the model is applied to the analysis of several practically important examples including cylindrical reinforced smart composite shells and multi-layer smart shells.
Keywords: Micromechanics; Thermoplastics; Civil engineering; Metals